Health education actions related to the biopsychosocial context and quality of life of university students in times of COVID-19: experience report (Research, Society and Development, 2022)
Objective: To report health education actions related to the biopsychosocial context and quality of life of university students. Methodology: This is an experience report, developed with students from a community university. For the development of health education actions, an action plan was first carried out, based on the five stages of the nursing process. Results and Discussion: A health education action was developed, aimed at increasing students' perception of how to prevent psychosocial disorders, in addition to seeking to provide aspects for an improvement in their quality of life. The educational materials developed were named: How to maintain mental health in a period of social isolation; Food for a healthy life; Physical activity: practice this idea; and Strengthening your self-esteem. Final considerations: Educational actions related to the biopsychosocial context have the role of promoting the health of undergraduate students, minimizing stressors, in addition to contributing to the improvement of quality of life.